Co-ordination of enterprise skill formation: a sociological and historical narrative of professional, market and state initiatives in South Africa - Lundall, Paul Arnold (Department of Sociology, 2019)
This thesis analyses the sociological and historical genesis of enterprise skill formation in South Africa and its effective coordination. South Africa’s late nineteenth century development as an emerging economy contributed to the state often taking the lead and being at the forefront of efforts to ensure coordination in enterprise skill formation. But gradually, concerns shaped by issues related to labour supply motivated leaders in firms and enterprises to forge their own imprint on the coordination of enterprise skill formation. The thesis also shows how these concerns with the coordination of enterprise skill formation involved intellectuals and professionals who attempted to intervene on these matters. The thesis proceeds to elaborate the unique institutional architecture which was constructed at various junctures in the history of South Africa’s human resource and skill formation journey. Furthermore the thesis gives an insight into the coordination of enterprise skill formation which occurred in the period of apartheid induced reforms. The evidence however shows that even when regimes change and new political orders are established, it does not end the necessity for continuity in the coordination of enterprise skill formation. As is to be expected, the institutional, regulatory and instrumental content of the coordination of enterprise skill formation is more complex in the contemporary period (circa. 2017) than it was in the 1920s and 1930s. However, the goal striven toward then was for a more streamlined process which could contribute to a change and improvement in the existing practice of enterprise skill formation. Evidence shows that this has been ongoing for over a century. The thesis gives an intricate and detailed insight into the process of building a new coordinated skills development system that was intended to ensure the coordination of enterprise skill formation under a democratic post-apartheid political dispensation. In this period a levy-grant system underwritten by a national skills levy has been a central instrument of direct coordination into enterprise skill formation. The analysis that is provided traces the iterative steps that were treaded by policy makers and policy thinkers from at least the early 1920s as they confronted what may have appeared as an elusive enterprise skill formation process. This analysis is done with a great deal more depth for the period since the early 1990s.